2007
DOI: 10.2304/ciec.2007.8.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Voices from the other Side of the Fence: Early Childhood Teachers' Experiences with Mandatory Regulatory Requirements

Abstract: Guided by feminist research principles, the study reported in this article contributes to the growing research dialogue on early childhood teachers' experiences with, and perceptions of, the impact of regulatory requirements on their teaching and on their perceptions of themselves as professionals. Specifically, three teachers from metropolitan Sydney (Australia) offered insights into their experiences working under the state of New South Wales (NSW) Children's Services Regulation 2004 ('the Regulation'), a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…On the whole, the teachers viewed themselves as playing a number of essential roles for the children and parents in their Kindergarten community. This experiencing of feeling inundated and pressured by the demands made upon them is congruent to the teachers' views shared in Bown & Sumison's (2007) study who through vivid, visual representation revealed their experience of feeling bound to an office chair and even sacrificing themselves, only to be to pecked apart one piece at a time by birds.…”
Section: Teachers' Perceptions Of Their Rolessupporting
confidence: 76%
See 2 more Smart Citations
“…On the whole, the teachers viewed themselves as playing a number of essential roles for the children and parents in their Kindergarten community. This experiencing of feeling inundated and pressured by the demands made upon them is congruent to the teachers' views shared in Bown & Sumison's (2007) study who through vivid, visual representation revealed their experience of feeling bound to an office chair and even sacrificing themselves, only to be to pecked apart one piece at a time by birds.…”
Section: Teachers' Perceptions Of Their Rolessupporting
confidence: 76%
“…Urban (2008) has already conceptualized the provision of policy framework documents to guide teachers in improving their programs as an example of the technicization of Early Childhood teaching. In similar vein, a growing number of findings resemble many of the challenges identified in other education sectors, including the de-professionalization of teachers, lack of empowerment experienced by early childhood teachers and reports of constrained practice (Overton, 2009;Bown & Sumison, 2007). There has been some research into the way in which Early Childhood Educators experience organizational change (Burgess & Fleet, 2009) and go about their work in response to reform agendas (Comber & Nixon, 2009).…”
Section: Literature Review: Teacher's Professional Practicementioning
confidence: 86%
See 1 more Smart Citation
“…Chubbuck & Zembylas (2007) describe the emotional life of a first-year teacher as complex and ambivalent. As more and more teachers are being pressured to conform to linear and standardized regimens of knowledge, studies are revealing how teachers are feeling constrained, scrutinized, and under surveillance by the political standards and power structures imposed upon them in this era of accountability (Brown & Sumsion, 2007).…”
mentioning
confidence: 99%
“…While not all early childhood teacher education programs operate in a high-stakes accountability context that requires teachers to implement a mandated curriculum and their students to pass tests for grade promotion and highschool completion, early education reforms that put in place particular content expectations, assessment measures, and teacher training requirements are making such learning environments more common in the U.S. (Stipek 2006) and across the globe (e.g., Brown and Sumsion 2007).…”
Section: Contextmentioning
confidence: 99%